OCCUPATIONAL SAFETY AND OCCUPATIONAL HEALTH (SMK3) BY PT. HUTAN SAWIT LESTARI IN TULAN HULU DISTRICT, EAST WARINGIN CITY DISTRICT CENTRAL KALIMANTAN PROVINCE - Kristiana, Tresia (JURNAL SOCIOPOLITICO, 2024)
Palm oil plantations are one of the strategic commodities that contribute to the country's foreign exchange, with an average of US$ 22-23 billion. Palm oil plantations are capable of absorbing a workforce of up to 16 million people directly. The area of oil palm plantations in 2022 will increase by 2.49% from the previous year. Riau Province is the area with the largest area of oil palm land in Indonesia, however the area of oil palm land does not have a significant effect on the amount of labor absorption. Central Kalimantan is the province with the largest number of oil palm plantation workers, reaching 756 thousand people. This number beats Riau's 609 thousand workers. PT. Lestari Palm Forest is one of the plantation companies in Central Kalimantan Province, located in Taulan Hulu District, East Kotawaringin Regency, with the largest number of palm oil plantation workers, reaching 1772 workers. Based on Law No.13 of 2003 concerning employment, PT. Sustainable Palm Oil Forests are required to implement an Occupational Safety and Health Management System (SMK3). This research uses qualitative methods, collecting data using in-depth interviews, observation and documentation studies. Key informants consist of elements from the leadership of PT Huntan Sawit Lestari, P2KT administrators, and environmental experts at PT Hutan Sawit Lestari, supervisors and employee representatives.Data analysis uses the triangulation method. The research data were analyzed using Van Meter and Van Horn's Policy Implementation theory. The research results it is known that the Plantation Company PT. Letasi Palm Oil Forest has implemented an Occupational Safety and Health Management System in accordance with statutory provisions. The company formed the P2KT organization as the implementing unit, and established supervisors. The company provides facilities and infrastructure in the form of equipment to prevent work accidents, provides health facilities in the form of health clinics, and installs signs to indicate danger. To support the performance of P2K3, the Company provides certified experts according to the required fields and from ministries and other institutions. Conclusions from this research Overall, the Palm Oil Plantation Company PT. Sustainable Palm Oil Forest has implemented Occupational Safety and Occupational Health principles in accordance with the mandate of Law No. 13 of 2003 concerning Labor in every line of work. However, it needs to be improved in order to achieve the common goal of Safety and Health at work and the ultimate goal is Zero Accidents. Companies are expected to make a priority scale by making adjustments to the latest regulations.